2018
DOI: 10.1037/ppm0000114
|View full text |Cite
|
Sign up to set email alerts
|

From bodies to blame: Exposure to sexually objectifying media increases tolerance toward sexual harassment.

Abstract: This paper investigates whether exposure to sexually objectifying media leads to more tolerance toward sexual harassment of women in the context of a real-life scenario. Moreover, given that self-objectification reflects the internalization of gender-based inequalities, we also tested whether self-objectification was associated with greater tolerance toward sexual harassment of women. Two hundred and ten undergraduate students (112 men) were asked to watch sexually objectifying (vs. neutral) video clips before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 72 publications
3
14
0
Order By: Relevance
“…Fox, Ralston, Cooper, and Jones (2015) found that women who self-objectified due to exposure to sexualized avatars showed greater endorsement of rape myths than women exposed to non-sexualized avatars. Moreover, trait self-objectification was found to predict tolerance toward sexual harassment and more negative attitudes towards harassed victims in both men and women (Bernard et al, 2016). Accordingly, one might expect internalized sexualization levels to be related to more lenient views of sexual harassment and higher skepticism about allegations of sexual misconduct made through the #MeToo movement.…”
Section: Views Of Sexual Harassmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Fox, Ralston, Cooper, and Jones (2015) found that women who self-objectified due to exposure to sexualized avatars showed greater endorsement of rape myths than women exposed to non-sexualized avatars. Moreover, trait self-objectification was found to predict tolerance toward sexual harassment and more negative attitudes towards harassed victims in both men and women (Bernard et al, 2016). Accordingly, one might expect internalized sexualization levels to be related to more lenient views of sexual harassment and higher skepticism about allegations of sexual misconduct made through the #MeToo movement.…”
Section: Views Of Sexual Harassmentmentioning
confidence: 94%
“…Past work has also highlighted positive associations between women's sexual objectification and tolerance of sexual harassment (Bernard, Ledrand, & Klein, 2016;Milburn, Mather, & Conrad, 2000;Read, Lynch, & Matthews, 2018). People exposed to sexualized images of women attribute more blame and responsibility to rape victims (Bernard et al, 2016;Burgess & Burpo, 2012;Loughnan, Pina, Vasquez, & Puvia, 2013;Ward, 2016).…”
Section: Views Of Sexual Harassmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexualized women, for example, are held responsible for sexual victimization (Burt, 1980), despite the blame for sexual aggression falling squarely on perpetrators. Indeed, sexually objectified women are misperceived as more responsible for sexual violence including sexual assault (Bernard, Gervais, Allen, Delmée, & Klein, 2015;Loughnan, Pina, Vasquez, & Puvia, 2013;Rudman & Mescher, 2012) and sexual harassment (Bernard, Legrand, & Klein, 2018;Galdi, Maass, & Cadinu, 2014) than their humanized counterparts.…”
Section: Self-objectifying Behaviorsmentioning
confidence: 99%
“…For instance, altering configural face information (i.e., by presenting faces in an inverted position) impairs the ability to categorize faces as human and as possessing human-like traits (Hugenberg et al, 2016). Testing whether cognitive objectification of face causes dehumanization would enable to uncover the potential negative consequences of face objectification and related dehumanization (e.g., victim blaming: Loughnan et al, 2013; tolerance toward sexual harassment: Bernard, Legrand, & Klein, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%